Ranking of tweets based on credibility factors / Pradeesh - Pradeesh, - (2017)
Twitter is extensively being used to share news, links, images and even have conversations. In Malaysia alone, there are 3.5 million twitter users. As the volume of tweets and users who are increasingly accessing tweets as source of information, they have less information to judge if a tweet is credible or not. The consequences of spreading non-credible tweets can be harmful to the society, nation and to the entire world. To respond to this issue, this research considered ranking tweets by various qualities of a tweet, such as popularity, reliability, timeliness, trustworthiness of web pages and tweets link to provide a more credible Twitter users search results than the current Twitter search which only looks at relevance without looking at the credibility of the tweet. An evaluation of the method on 144,972 tweets from GST which is consists of Malay and English tweets shows that the proposed scoring technique pTRank scores much more better compared to TwitterRank in various ranking evaluations such as in Normalized Discounted Cumulative Gain (nDCG), the system scored a score of 0.393, as opposed to TwitterRank which is at 0.121. The same trend is also noticed with both GST tweets in both the languages and as well as only on English.